Process integration as a tool for energy systems analysis : application to LKAB in Kiruna - Sandberg, Johan (Luleå tekniska universitet, Energivetenskap, 2011)
In recent years, increased concern over global warming has put focus on the emissions of fossil CO2 into the atmosphere. Due to a strong relationship between the use of energy and the burning of fossil fuels, reducing society’s energy use has become increasingly important. In the energy intensive process industry, process integration is a field of research that has shown good results for decreased energy use in many industrial branches. This thesis is centred on the introduction of process integration to a new industrial branch for the field ‐ the mining industry. With an overall aim to introduce process integration as a tool for increased energy efficiency of Loussavaara‐Kiirunavaara AB (LKAB) in Kiruna, the application and development of process integration methods is presented. More specifically the thesis deals with process systems modelling by application of the MIND method (Method for analysis of INDustrial energy systems) and the optimisation of those models by MILP (Mixed Integer Linear Programming) optimisation. Among the results of this thesis are; the presentation of optimised operational strategy for utility boilers that can decrease fuel use with 7%, thedevelopment of a new method for facilitated multi‐period optimisation of dynamic systems and the proposal of a heat recovery installation in the mine ventilation system capable of decreasing the heating systems fuel use by 67%.